Actitudes de los padres hacia el retardo mental leve de sus hijos en una muestra de la provincia constitucional del Callao - Pequeña Constantino, Juan (2003)
The attitudes of the parents are evaluated towards the children with Mental Retardation, through a comparative descriptive study. The sample was conformed by the parents, of 54 children with I diagnose of Mental Retardation selected of the Educative Centers of Special Education of the Callao, for it was used like instrument a Scale type Likert de Actitudes of the mother towards the son with Mental Retardation, as much in its version for the son like for the daughter. The results indicated that significant differences between the parents and the mothers as far as the general attitudes were not reached, and in the areas of Well taken care of Protection, Perception and Acceptance of the Problem Interpersonal Prejudices, Discipline, Relations, Expectations of Profit and Familiar Integration, according to the sex of the son separately. Significant differences were not reached either when single comparing in the parents their attitudes towards the son and the single daughter and in the mothers these attitudes. One concludes that the parents and the mothers have attitudes similar front to their son with mental retardation. Finally, it is recommend to make studies that consider the different socioeconomic status with the purpose of being able to generalize the information.